2016
DOI: 10.1097/md.0000000000004768
|View full text |Cite
|
Sign up to set email alerts
|

Spindle cell carcinoma of the esophagus

Abstract: This study conducted a retrospective multicenter analysis to investigate the clinicopathological features, optimal therapeutic strategy, and prognosis of spindle cell carcinoma (SpCC) of the esophagus.A total of 71 patients with esophageal SpCC from 3 large cancer centers in China were systematically analyzed. All patients received curative resection, 13 patients received adjuvant radiotherapy and 15 patients received adjuvant combination chemotherapy. Additionally, a total of 1852 patients with typical esopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…More than 80% of tumors are limited to the submucosa or muscularis propria at presentation. [ 14 ] Zhang et al [ 11 ] reported the percentage of T1/2 lesions was higher in the ECS group than in the ESCC group (67.6% vs 29.7%, P < .001), which was similar to Liang Wang reported (20/33, 60.6%). [ 4 ] Therefore, some investigations supported therapeutic endoscopy, including endoscopic polypectomy, endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD), which may represent an alternative to esophagectomy for superficial esophageal carcinosarcoma [ 15 ] and are more tolerable, less invasive, less expensive, notably, it enables the esophagus to be preserved, compared with traditional esophagectomy.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…More than 80% of tumors are limited to the submucosa or muscularis propria at presentation. [ 14 ] Zhang et al [ 11 ] reported the percentage of T1/2 lesions was higher in the ECS group than in the ESCC group (67.6% vs 29.7%, P < .001), which was similar to Liang Wang reported (20/33, 60.6%). [ 4 ] Therefore, some investigations supported therapeutic endoscopy, including endoscopic polypectomy, endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD), which may represent an alternative to esophagectomy for superficial esophageal carcinosarcoma [ 15 ] and are more tolerable, less invasive, less expensive, notably, it enables the esophagus to be preserved, compared with traditional esophagectomy.…”
Section: Discussionsupporting
confidence: 60%
“…The clinical features of ECS is similar to that of ESCC with dysphagia as the most prominent and frequent symptom, [ 10 , 11 ] and sometimes with chest pain and weight loss. More than 80% of ECS are located in the middle and/or lower esophagus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding preoperative diagnosis, Zhang et al[ 18 ] and Hashimoto et al[ 4 ] reported that 14.1% (10/71) and 17.9% (5/28) of esophageal carcinosarcomas, respectively, were suspected to have sarcomatous components based on biopsy. Although imaging and endoscopy showed characteristic features, preoperative diagnosis was still difficult.…”
Section: Discussionmentioning
confidence: 99%